The role of self-awareness and learning discipline during distance learning in urban students - Eka Putri Azrai; Erna Heryanti; Nandita Fazriati (Biosfer: Jurnal Pendidikan Biologi, 2026)
Conceptual understanding is an essential component in achieving meaningful learning outcomes in biology. During distance learning, students are required to regulate their learning independently, making self-awareness and learning discipline important factors that may influence their conceptual understanding. This study aimed to examine the role of self-awareness and learning discipline in distance learning in improving students’ conceptual understanding of drug-related material among urban high school students. The research employed a quantitative descriptive correlational design. The study was conducted in a public high school in Jakarta, Indonesia, involving 85 grade XII science students selected through simple random sampling. Data were collected using validated instruments measuring self-awareness, learning discipline, and conceptual understanding. Data analysis included descriptive statistics, prerequisite tests, and regression analysis. The results showed that students’ self-awareness and learning discipline were generally in the high category. Regression analysis indicated that self-awareness and learning discipline together contributed 7.1% to students’ conceptual understanding of drug material, while 92.9% was influenced by other factors. These findings suggest that although self-awareness and learning discipline play a role in supporting conceptual understanding during distance learning, other internal and external factors should also be considered to improve students’ learning outcomes.